KAJIAN SOSIOLINGUISTIK PEMAKAIAN KODE BAHASA MASYARAKAT DWIBAHASA DI KABUPATEN ENREKANG - Eli, Eli (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2023)
Communication using language in everyday life is important noticed. The use of language is means convey the message from the speaker to his partner. The use of cross-cultural languages that have different social systems will bring up variations in the use of language and the language code used. This study aims to explain the variations and social factors that determine the choice of code by Javanese speakers in Enrekang District. This research is field research and the method used in this study is the ethnographic method with a sociolinguistic approach that focuses on studying communication patterns used by speech communities so that the data obtained form of qualitative data. The results of the study show that there are at least 4 codes in the Javanese speech community, namely Indonesian (BI), Bahasaarea language (BL), a foreign language (BA) and the speaker's native language, namely Javanese (BJ). The social factors that determine the choice of language code are domain factors, norms and speech participants. The results of this study contribute to the treasures of sociolinguistic theory, especially in code mixing and code switching.Study This is important to carry out to reveal the phenomena of language and socio-cultural life in a dynamic society, while in terms of code mixing and code switching this research sharpens opinions about the factors that cause the use of code switching and code mixing